2021
DOI: 10.1109/access.2021.3056505
|View full text |Cite
|
Sign up to set email alerts
|

A Black Box Tool for Robustness Testing of REST Services

Abstract: REST services are nowadays being used to support many businesses, with most major companies exposing their services via REST interfaces (e.g., Google, Amazon, Instagram, and Slack). In this type of scenarios, heterogeneity is prevalent and software is sometimes exposed to unexpected conditions that may activate residual bugs, leading service operations to fail. Such failures may lead to financial or reputation losses (e.g., information disclosure). Although techniques and tools for assessing robustness have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…Based on the previous results, we can conclude that foREST has non-trivial performance advantages over RESTler and EvoMaster in fuzzing RESTful APIs. Note that that are also other tools that support RESTful API fuzzing, such as RestTestGen [25] and bBOXRT [18]. However, an empirical study [8] has shown that these tools are either preliminary or not robust compared to RESTler, and RESTler is the best one over them.…”
Section: Comparison With Existing Toolsmentioning
confidence: 99%
“…Based on the previous results, we can conclude that foREST has non-trivial performance advantages over RESTler and EvoMaster in fuzzing RESTful APIs. Note that that are also other tools that support RESTful API fuzzing, such as RestTestGen [25] and bBOXRT [18]. However, an empirical study [8] has shown that these tools are either preliminary or not robust compared to RESTler, and RESTler is the best one over them.…”
Section: Comparison With Existing Toolsmentioning
confidence: 99%
“…bBOXRT is a black-box robustness testing tool for RESTful APIs proposed by Laranjeiro et al [7], written in Java and available on the authors' website 7 . The aim of bBOXRT is to assess the robustness of REST APIs observing the behavior of services under test when providing invalid requests.…”
Section: Bboxrtmentioning
confidence: 99%
“…To the best of our knowledge, the only black-box testing approaches for REST APIs which provide an implementation, i.e., a usable testing tool, are the one we have taken into account in our comparison (RestTestGen [5], RESTler [6], bBOXRT [7] and RESTest [8], presented in Section III). Regarding test coverage, the only work proposing a systematic approach to assess the coverage of REST APIs testing tools is the framework of Martin-Lopez et al [3], that we have taken as basis for our comparison.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, deep learning models have been proposed to determine the validity of these inputs [32]. The generated tests can assess the robustness of the API through invalid requests [33], detect regressions across API versions [34], verify the data dependencies among sequences of requests [35], or verify the constraints imposed on their parameters [36]. Metamorphic relations among requests may also serve as the oracle [37].…”
Section: A Test Generation For Web Apismentioning
confidence: 99%